Influence of intramuscular fiber orientation on the Achilles tendon curvature using three-dimensional finite element modeling of contracting skeletal muscle. Issue 14 (3rd October 2016) - Kinugasa, Ryuta; Yamamura, Naoto; Sinha, Shantanu; Takagi, Shu
Abstract: Tendon curvature plays a key role in mechanical gain (amplifying the joint excursion relative to fiber length change) during joint motion, but the mechanism remains unresolved. A three-dimensional finite element (FE) model was used to investigate the influence of intramuscular fiber orientation upon the curvature pattern of the Achilles tendon during active muscular contraction. Two simulation models, with fiber pennation angles of θ = 25° and 47° were tested for the gastrocnemius and soleus muscles. A smaller pennation angle (25°) of the soleus muscle fibers was accompanied by a large change in curvature whereas a larger pennation angle (47°) of the soleus muscle was accompanied by small effects. These results suggest that the fiber pennation angle determines the curvature of the tendon, and the magnitude of the curvature varies along the length of the aponeurosis. Such FE modeling has the potential of determining changes in force output consequent to changes in intramuscular fiber orientation arising from resistance training or unloading, and provides mechanism for predicting the risk of Achilles tendon ruptures.